Institutional relatedness behind product diversification and international diversification - Sun, S.; Peng, Mike; Tan, W. (Springer New York LLC, 2017)
© 2017 Springer Science+Business Media New YorkPrevious diversification research has largely focused on product relatedness, but ignored institutional relatedness—the degree of informal embeddedness with the dominant institutions that confer resources and legitimacy. We argue that during institutional transitions, political ties and international experience represent different types of institutional relatedness linking firms, respectively, to political institutions and market institutions. Specifically, CEOs’ political ties may help firms access critical resources, sense new market entry opportunities, and gain board support to increase firms’ product diversification. CEOs’ international experience may help firms leverage different market-based capabilities, engage in international competition, and then lead firms to grow on a different path by expanding internationally. We further investigate a crucial contingency factor: the degree of economic freedom. Data from 11,992 firm-year observations based on firms listed on China’s stock exchanges between 2001 and 2011 largely support our predictions.